Novice And Experienced English Teachers’ Strategies For Teaching English In Junior High School - Komang Radi Ananda Triawan (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study aims to analyze the teaching strategies employed by novice and experienced English teachers at SMP Negeri 6 Singaraja. The research specifically focuses on identifying the types of teaching strategies used by both groups, examining how teaching experience influences the choice of strategy, and comparing the differences between the two groups. The study employed a descriptive qualitative method, collecting data through observations, interviews, document checklists, and anecdotal notes. The results showed that novice teachers tend to use more student-centred and modern teaching strategies, including project-based learning, discovery learning, and integration of digital technologies such as games and multimedia. These strategies aim to actively engage students and encourage collaboration through technology-based platforms such as PowerPoint, Quiz, and WhatsApp. However, the strategies employed are still less structured and continue to evolve. On the other hand, experienced teachers demonstrate a more balanced approach, incorporating both traditional and modern strategies, such as cooperative learning, problem-based learning, metacognitive strategies, and active learning. The comparison shows that novice teachers are more explorative with technology and emphasize student engagement, while experienced teachers are more strategic and adaptable, combining conventional and contemporary approaches effectively. The findings suggest that teaching experience has a significant impact on the choice and application of teaching strategies in the EFL classroom context. However, the study's limited sample size and short duration may affect the generalizability of the findings. Further research is needed to explore its long-term impact and the application of this method in broader educational settings.